HEALTH EVALUATION OF PT BANK SYARIAH INDONESIA TBK (BSI) THROUGH THE RBBR METHOD: A REVIEW OF THE PERIOD 2014-2023 - Nurhayati, Anggita; Suwantri, Kristiana; Nengtias , Defia Oktaviana (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the financial health of PT Bank Syariah Indonesia Tbk (BSI) from 2014 to 2023 using the Risk-Based Bank Rating (RBBR) method. The research focuses on evaluating key financial indicators, including Non-Performing Financing (NPF), Good Corporate Governance (GCG), Return on Assets (ROA), and Capital Adequacy Ratio (CAR), to assess BSI's performance, challenges, and risk management strategies. Method: The analysis employs the RBBR method, as outlined in OJK Circular Letter No.14/SEOJK.03/2017, to evaluate BSI's financial health. This method assesses four main aspects: Risk Profile (measured using NPF), Good Corporate Governance (GCG), Earnings (measured using ROA), and Capital (measured using CAR). Data was collected from financial reports, regulatory publications, and relevant literature, and was processed to determine BSI's financial health score. Results: The findings indicate that BSI maintained a stable financial health score, fluctuating between the